The interaction between the changing agri-food supply chain systems and smallholder farmers of Gauteng, South Africa . - Makaepea, Motlatjo George. (My University, 2014)
ABSTRACT The research proposes to evaluate the interaction between the “changing agri-food supply chain systems” and smallholder farmers of Gauteng Province and challenges and opportunities for their integration into mainstream agri-industrialized markets. The objectives of the research were: - to evaluate perceptions of Gauteng small-holder farmers to the changes in agri-food supply chain systems of South Africa - to determine challenges and opportunities of Gauteng smallholder farmers `s integration into mainstream agri-industrialized and formal markets such as contract farming A survey questionnaire was designed utilising a seven-point Likert scale and administered to the targeted respondents for the collection of data. The questionnaire comprised of various questions and statements representing the constructs as well as questions aimed at collecting various demographic data. The data was analysed using descriptive statistics which includes factor analysis and analysis of variance. The results of the analysis were used to answer each research proposition as well as to formulate findings and recommendations. The main findings of this research showed that 42% of the farmers surveyed had understanding of business strategies comprised of appropriate production plans and marketing plans. 34% of farmers surveyed demonstrated understanding of the changing nature of the agri-food supply chain with regard to technology, globalisation & other factors driving change. 20% of the farmers surveyed had the knowledge and understanding of contract farming and had at least participated in such a contract once. In relation to knowledge of quality assurance pertaining to food safety, traceability and grading standards; only 16% of the farmers surveyed had the knowledge of certification programs such as GlobalGAP and HACCP. The same percentage of farmers was found to have worked with marketing agents in selling their produce. It was furthermore determined that large proportion of smallholder farmers (62%) preferred to market their products through alternative food supply networks such as farmers markets and 70% believed in community supported agriculture. Specific recommendations were developed for the smallholder farmers. Additional set of recommendations were developed to specify the role that government and industry can play in contributing to the development of smallholder farmers. Key recommendations are centred on development of various programs which address:  Business management and entrepreneurial skills development  Increasing number of smallholder farmers who becomes accredited and compliant with good standards & grades, food safety and quality assurance programs such as GlobalGAP and HACCP.  Assisting smallholder farmers to exploit their comparative advantage in alternative food supply networks through increased platforms such as farmers markets, building local and regional brands which consumers can associate with geographically.  Government must facilitate value-chain development with regard to ensuring smallholder farmers participation. State institutions must serve as major market points for produce of small farmers.  Both supply side and demand-side agro-industry must contribute to assisting farmers with support services (e.g. access to information on improved crops, better pest management practices and products, improved product handling, changes to buyer requirements) to mitigate changes in the food supply chain.  A program to assist smallholder farmers with increased production infrastructure to attain economies of scale where smallholder farmers are currently producing to maximum capacity is encouraged. This should include post-harvest handling facilities.  Government must consider tax-incentivising large agro-processing companies and large retailers to source their products from smallholder farmers’ co-operatives.
MBA 2013
Keywords: Farms,Food industry and trade,Food supply